Pertumbuhan Batang Bawah Karet pada Beberapa Komposisi Media Tanam dalam Root Trainer - Junaidi Junaidi; Atminingsih Atminingsih; Eka Boby Febrianto; Rina Maharany Maharany (Jurnal Ilmu Pertanian Indonesia, 2021)
The rubber tree rootstock nursery using the root trainer method is aimed to promote root growth through the use of non-soil growing media in a special container. This technology offers the advantages of a shortened breeding process, good rooting, and ease of delivery. The objective of this study is to investigate the effect of the planting media composition of oil palm bunches compost, manure, rice husk, solid decanter, and Trichoderma viride on the growth of rubber rootstock under the root trainer method. The research was carried out in the greenhouse of the Sungei Putih Research Center, Indonesian Rubber Research Institute, Deli Serdang, North Sumatra in January-May 2019. The observation included plant height, number of leaves, stem diameter, dry weight, and root length, and successful grafting percentage. The results indicated that the mixture of oil palm bunches compost, solid decanter, and Trichoderma viride (Te treatment) was the most potential to be developed as a planting media for rubber rootstock nursery under root trainer system. At 18 weeks after planting, the Te treatment had an average height of 82.66 + 14.27 cm with an increment rate of 3.25 + 0.81 cm/week, number of leaves 11.33 + 3.21 leaves with the increment of 0.52 + 0.20 leaves/week, stem diameter 5.29 + 0.73 mm with an increase of 0.33 + 0.05 mm/week. The Te treatment had a length and root weight of 41.97 + 2.40 cm and 1.68 + 0.77 g, respectively, with the grafting successfulness percentage of 47.37%. Besides showing good growth, these materials are also available in large and continuous quantities. The use of Trichoderma viride not only for increasing plant growth but also as a biocontrol of white root disease. Keywords: growth, growing media, Hevea brasiliensis, rootstock, root trainer